A comparatlve study on the performance of pick-up and stationary baler for baling rice and wheat straw l - EI-Khateeb, Hamada; Khodeir, M. A.; Soliman, AbdelGawad (2011)
The peiformance of the pickup baler in terms of field capacity, field efficiency, bale density, baling losses, size requirements for storing bales, power, energy and cost was investigated as a function ofchange in baler fonvard speed, and material moisture content during baling rice straw,and wheat straw under the following conditions: Generally, by increasing the baler forward speed from (/.5 to 5.5 km/h) tends to increase the feed rate from (/.4 to 3.0 Mg/h), baler losses from (-10 to 60%), bale density from (82.0 to 89.0 kg/ m3 ), actual field capacity from (0.35 to 1. 22 fed/h) and power requiredfrom (65 to //.0 kW) during baling rice straw. The results also showed that by increasing the materials moisture content from (/1.0 to 24.0 %) tends to increasing thefeed rate from (1.4 to 2.5 Mg/h), baler losses from (4.0 to 7.0 %) and bale density from (82.0 to /00.0 kg/ m3 ) during baling rice straw.
Includes references.
Summary in Arabic.
1
Keywords: Rice -- Machinery; Wheat straw -- Machinery